A lysin motif effector subverts chitin‐triggered immunity to facilitate arbuscular mycorrhizal symbiosis. Issue 1 (23rd November 2019) - Zeng, Tian; Rodriguez‐Moreno, Luis; Mansurkhodzaev, Artem; Wang, Peng; van den Berg, Willy; Gasciolli, Virginie; Cottaz, Sylvain; Fort, Sébastien; Thomma, Bart P. H. J.; Bono, Jean‐Jacques; Bisseling, Ton; Limpens, Erik
Summary: Arbuscular mycorrhizal (AM) fungi greatly improve mineral uptake by host plants in nutrient‐depleted soil and can intracellularly colonize root cortex cells in the vast majority of higher plants. However, AM fungi possess common fungal cell wall components such as chitin that can be recognized by plant chitin receptors to trigger immune responses, raising the question as to how AM fungi effectively evade chitin‐triggered immune responses during symbiosis. In this study, we characterize a secreted lysin motif (LysM) effector identified from the model AM fungal species Rhizophagus irregularis, called RiSLM. RiSLM is one of the highest expressed effector proteins in intraradical mycelium during the symbiosis. In vitro binding assays show that RiSLM binds chitin‐oligosaccharides and can protect fungal cell walls from chitinases. Moreover, RiSLM efficiently interferes with chitin‐triggered immune responses, such as defence gene induction and reactive oxygen species production in Medicago truncatula. Although RiSLM also binds to symbiotic (lipo)chitooligosaccharides it does not interfere significantly with symbiotic signalling in Medicago . Host‐induced gene silencing of RiSLM greatly reduces fungal colonization levels. Taken together, our results reveal a key role for AM fungal LysM effectors to subvert chitin‐triggered immunity in symbiosis, pointing to a common role for LysM effectors in both symbiotic and pathogenic fungi.